Peranan Kelompok Teman Sebaya di Sekolah dalam Meningkatkan Komunikasi Interpersonal Siswa - Isti’adah, Feida Noorlaila; Permana, Rahmat (Psikopedagogia, 2017)
This study aimed to find out to what extent the role of peer group at school towards the students’ interpersonal communication This was a descriptive quantitative study. The  number of subject of  this study were 172 students of class the tenth-grade students of all vocational high school in Singaparna sub-district  with taken by using simple random sampling. The data of this study were analyzed statistically by using linear regression test, the coefficient of correlation test, and coefficient of determination test. Based on the data analysis, This study found that there was a significant relationship between peer group at school and students’ interpersonal communication. The result of this study was beneficial for school counselor in directing the students about the importance of positive interaction within the peer group and the importance of developing the students' interpersonal communication.